2020
DOI: 10.3390/nano10112208
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Gallium Oxide—A Review from Synthesis to Applications

Abstract: Spinel ZnGa2O4 has received significant attention from researchers due to its wide bandgap and high chemical and thermal stability; hence, paving the way for it to have potential in various applications. This review focuses on its physical, optical, mechanical and electrical properties, contributing to the better understanding of this material. The recent trends for growth techniques and processing in the research and development of ZnGa2O4 from bulk crystal growth to thin films are discussed in detail for dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 119 publications
1
25
0
Order By: Relevance
“…The zinc gallate spinel (ZnGa 2 O 4 ) has been widely studied for optical applications such as flat panel displays, [1,2] saturable absorbers, [3] in vivo bio-imaging applications, [4][5][6] thermal sensors, [7,8] X-ray dosimetry, [9] optoelectronics, [10,11] anti-counterfeiting applications. [8,12,13] ZnGa 2 O 4 crystallizes in a cubic direct "AB 2 O 4 " spinel structure with the Fd3̅ m space group in which Zn 2+ ions occupy the tetrahedral A-sites and Ga 3+ the octahedral B-sites. [14] It can exhibit different emission colors when doped with transition metal elements.…”
Section: Introductionmentioning
confidence: 99%
“…The zinc gallate spinel (ZnGa 2 O 4 ) has been widely studied for optical applications such as flat panel displays, [1,2] saturable absorbers, [3] in vivo bio-imaging applications, [4][5][6] thermal sensors, [7,8] X-ray dosimetry, [9] optoelectronics, [10,11] anti-counterfeiting applications. [8,12,13] ZnGa 2 O 4 crystallizes in a cubic direct "AB 2 O 4 " spinel structure with the Fd3̅ m space group in which Zn 2+ ions occupy the tetrahedral A-sites and Ga 3+ the octahedral B-sites. [14] It can exhibit different emission colors when doped with transition metal elements.…”
Section: Introductionmentioning
confidence: 99%
“…Cr‐doped zinc gallate has good long afterglow emissions in red and near‐infrared regions 10–13 . Spinel ZnGa 2 O 4 has a wide band gap (4.4–5.0 eV), high chemical stability, and thermal stability 14–18 . In the process of practical application, long afterglow materials will confront harsh environments such as damp, high, or low temperatures, leading the afterglow performance to decline or even disappear.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Spinel ZnGa 2 O 4 has a wide band gap (4.4-5.0 eV), high chemical stability, and thermal stability. [14][15][16][17][18] In the process of practical application, long afterglow materials will confront harsh environments…”
mentioning
confidence: 99%
“…Wide bandgap semiconductors improve the efficiency of power-conversion stages, and they may be utilized instead of silicon in the production of voltage converters, power MOSFETs, and high-efficiency Schottky diodes. These can then be employed in electric and hybrid cars [ 11 ]. Recently, Chi et al and Chikoidze et al demonstrated the p-type ZnGa 2 O 4 semiconductor (5 eV), which could pave the way for bipolar oxide energy electronics by reducing switching and conversion losses.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to ZnGa 2 O 4 ′s combination of the required qualities for sustaining large electrical fields in p-n junctions in the off-state, together with low losses in the on-state [ 12 , 13 ]. ZnGa 2 O 4 possesses the cubic symmetric spinel structure with the space group of Fd m, where Zn 2+ cations occupy tetrahedral sites and Ga 3+ cations occupy octahedral sites with oxygen atoms in close-packed cubic structures [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%